KEBERLANJUTAN BELAJAR MEMBACA SISWA SEKOLAH DASAR DI LUAR WAKTU SEKOLAH DI KECAMATAN KERUAK - Baiq Shelyna Zunaera; Nahdi, Khirjan; M. Deni Siregar; Muhammad Sururuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The continuity of reading learning outside school hours is important for strengthening elementary school students' literacy skills through the connection between school and home learning experiences. This study describes the continuity of students' reading after school hours, teachers' roles in directing home reading activities, and family support in building students' literacy practices. Its urgency lies in the importance of consistent reading habits, given that most students' learning time occurs outside school. Its novelty lies in analyzing reading continuity through the connection of three components: teacher strategies, students' reading activities after school, and family support as one literacy ecosystem. This descriptive qualitative study involved two teachers, ten students, and ten parents or guardians of elementary school students in Keruak District. Data were obtained through interviews, observation, and documentation, then analyzed through data reduction, data display, interpretation, and conclusion drawing. The results show three main findings. First, students' reading activities after school have taken place but have not become a consistent habit, still depending on teachers' assignments and directions. Second, teachers have built literacy reinforcement through reading activities, assignments, and communication with families, with varying intensity. Third, parents support reading through reminders, motivation, and guidance, but home literacy practices are not yet fully structured. The study concludes that reading-learning continuity requires stronger connections among teacher strategies, students' reading habits, and family support.